Excimer to exciplex transition through realization of donor-acceptor interactions in luminescent solvent-free liquids - Wakchaure, Vivek Chandrakant; Goudappagouda; Das, Tamal; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Nanoscale, 2021)
Luminescent solvent-free organic liquids are known for their enhanced quantum yield, color tunability, and availability of a matrix for other dopants to generate hybrid luminescent materials with improved features for newer applications. Herein, we report a donor-acceptor based luminescent ``exciplex liquid'' by utilizing the slightly different electron affinity of the acceptor molecules. A red-shifted broad exciplex emission exhibited by the donor-acceptor pair even at a lower concentration of the acceptor (0.001 equiv.) indicates high efficiency in the solvent-free state. A detailed NMR study revealed weak intermolecular interactions between the donor and acceptor in the solvent-free matrix that stabilizes the exciplex liquid. The failure of structurally similar solid counterparts to form an exciplex confirms the advantage of the available supportive liquid matrix. Besides, the luminescent exciplex liquid is found efficient in sensing application, which is unachievable by either the individual liquids or their solid counterparts. Here, a transition of a donor-acceptor pair from a solid to solvent-free liquid results in a new hybrid liquid that can be an alternative for solid sensor materials.